REPRESENTASI PEREMPUAN DALAM FILM LITTLE WOMEN (STUDI ANALISIS SEMIOTIKA) - Cornelia Larasati Anggraeni; S. Rouli Manalu; Triyono Lukmantoro (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Gender equality is a social issue that develops and challenges dynamically from time to time, especially for women. Challenges or even obstacles surrounding the issue of gender equality cannot discredit the development of gender equality which has started to moving to a better direction. Gender equality as a part of women's rights declared by the United Nations Human Rights has one specific issue that is still being faced by women today, that is women and choice. This narrative related to women and choice is also contained in a film as a form of popular culture. Especially, the Little Women (2019) adaptation by Greta Gerwig. This study describes how the film Little Women represents women in making decisions to choose by implementing John Fiske's semiotic theory to analyse the symbolization of women and choice through the level of reality, the level of representation and the level of ideology. Women and choices in the film Little Women are found in four categories, such as creative choice, marriage choice, career choice, and the way women think in making decisions. Through categories related to creative choice, this film depicts that women must follow the dominant ideology of the creative industry before finally having the opportunity to negotiate their wishes. The dominant ideology that emerges in creative choices is the conception of capitalism and patriarchy. Through the category of marriage choice, this film limits women in that they are depicted as having to go through the marriage path and that marriage is only limited to two conditions. These conditions led to the dominant ideology of materialism and patriarchy. Through the category of career choice, this film negates the notion of economic independence for women. Through the category of women's way of thinking, this film contains the ideas of existentialist feminism which emphasizes the independence and independence of women. The film Little Women offers a form of women's struggle to make decisions about certain choices. But actually, the choice taken by women is not a free will, but is a form of conditioning that society does to women.